Patient experiences of cancer care: scoping review, future directions, and introduction of a new data resource: Surveillance Epidemiology and End Results-Consumer Assessment of Healthcare Providers and Systems (SEER-CAHPS) - Michelle Mollica (The Beryl Institute, 2017)
The shift towards providing high value cancer care has placed increasing importance on patient experiences. This scoping review summarizes patient experience literature, highlights research gaps, and provides future research directions. We then introduce a new resource that links the National Cancer Institute’s Surveillance Epidemiology and End Results (SEER) program with the Centers for Medicare and Medicaid Services Consumer Assessment of Healthcare Providers and Systems (CAHPS) survey and longitudinal medical claims data. We conducted a scoping review to identify relevant research within the Medicare CAHPS domain that examine factors associated with patient-reported experiences with their cancer care. Gaps indicate a need for population-based research to explore relationships between cancer patient experiences, healthcare utilization, and subsequent patient outcomes. SEER-CAHPS, a publicly accessible data resource, may assist in addressing these gaps by linking cancer registry (SEER), survey data reported by Medicare beneficiaries (CAHPS), and Medicare claims, providing unique insight into quality of care. Linked data include 231,089 surveys from patients with a cancer diagnosis, and 4,236,529 surveys from patients without a cancer diagnosis. Results indicate substantial gaps in our knowledge of patient experiences and the need for additional resources. SEER-CAHPS links direct patient feedback with cancer registry and Medicare claims, making it an important source of information on experiences and healthcare utilization. Increasing recognition of the importance of patient-centeredness points to the need for population-based studies. Findings from SEER-CAHPS will inform initiatives to improve care delivery.